Incorporating ‘Ahmad Dahlan Values’ in the Curriculum of Higher Education - Endro Dwi Hatmanto (Ahmad Dahlan Journal of English Studies, 2018)
In 2012 the Directorate General of Higher Education of Indonesia required all higher education institutions to implement the Curriculum of Higher Education. As a part of higher education institutions, English Education Department of Universitas Muhammadiyah Yogyakarta has been implementing this curriculum for five years.  Curriculum of Higher Education has shifted the old paradigm of teacher-centered learning to the new pedagogical approach called student-centered learning. The implementation of the Curriculum of Higher Education necessitates all study programs to alter their curriculum oriented to produce competent graduates. English Education Department of Universitas Muhammadiyah Yogyakarta has also been making attempts to incorporate the Muhammadiyah values proposed by its founder, KH. Ahmad Dahlan. The research is aimed at exploring how the Ahmad Dahlan’s’ values are implemented in the CHE setting at the EED of UMY. The data were collected by means of interviews with a head of department and two lecturers, teaching observation, and document analysis and focus group discussion with 33 students.  The research found that the principles proposed by Ahmad Dahlan including the curriculum structure, pedagogical techniques, and character education had been successfully incorporated in the implementation of CHE and the Ahmad’s Dahlan values’ correspond to the CHE principles.